Pathology and morphometry of Hystrichis acanthocephalicus (Nematoda) from Phimosus infuscatus (Pelecaniformes) in southern Brazil - Scheer,Simone (2017)
Abstract Species of Hystrichis are parasite nematodes of the digestive tract of aquatic birds in South America, Europe and Asia. In Brazil, Hystrichis acanthocephalicus has been reported in Phimosus infuscatus. There are few data on the morphometry of this species and there are no reports on pathological conditions that it causes. Therefore, the purpose of this study was to report morphometric data from H. acanthocephalicus and describe the pathological effects of this parasite on the Phimosus infuscatus proventriculus. Thirty gastrointestinal tracts of P. infuscatus were examined to search for nematodes and H. acanthocephalicus occurred in 83% of hosts. Were measured the total length and body width of males and females, and of their respective cuticular spines, esophagus, spicules and eggs, and the internal and external diameter of copulatory bursa. Histopathological examination revealed parasitic structures in the proventriculus from the lumen (anterior end) to the outer layers of the organ (intermediate and posterior parts), in which we observed inflammatory reaction with infiltration of heterophils, hemorrhage and hemosiderin. The results of this study of histopathology, morphometry and parasitological indices are the first ones reported to H. acanthocephalicus and should contribute to the identification and recognition in cases of outbreaks in the Neotropical region.